2009
DOI: 10.1111/j.1365-2672.2009.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Key role of teichoic acids on aflatoxin B1binding by probiotic bacteria

Abstract: Aims:  To assess the ability of five probiotic bacteria to bind aflatoxin B1 and to determine the key role of teichoic acids in the binding mechanism. Methods and Results:  The strains were incubated in aqueous solutions containing aflatoxin B1 (AFB1). The amount of free toxin was quantified by HPLC. Stability of the bacteria–aflatoxin complex was evaluated by repeated washes with buffer. In order to understand the binding process, protoplasts, spheroplasts and cell wall components of two strains were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 45 publications
(136 reference statements)
6
75
0
2
Order By: Relevance
“…This evidence strongly supports the first mechanism that the toxin is removed predominantly by noncovalent binding with the chemical components of the bacterial cell wall. This mechanism is further evidenced by the reports of HernandezMendoza et al (2009) [41] who demonstrated that cell components such as teichoic acids are the possible binding sites for AFB1.…”
Section: Effect Of Lab and Mechanisticmentioning
confidence: 51%
See 2 more Smart Citations
“…This evidence strongly supports the first mechanism that the toxin is removed predominantly by noncovalent binding with the chemical components of the bacterial cell wall. This mechanism is further evidenced by the reports of HernandezMendoza et al (2009) [41] who demonstrated that cell components such as teichoic acids are the possible binding sites for AFB1.…”
Section: Effect Of Lab and Mechanisticmentioning
confidence: 51%
“…bulgaricus, and Bifidobacterium lactis), alone or in combination, in UHT (ultrahigh temperature) skim milk. On the other hand, other researchers showed that the binding ability of AFB1 to LAB is strain specific [18,34,41]. Regarding the effect of pH change during ergo fermentation, Elsanhoty et al (2014) [18] considered the pH change during fermentation as a factor affecting the binding interaction and showed an increase in the level of AFM1 reduction by the decrease in pH during bacterial treatment.…”
Section: Effect Of Lab and Mechanisticmentioning
confidence: 99%
See 1 more Smart Citation
“…In reference [57] authors explained that the integrity of the bacterial cell wall is important in the process of toxin removal by both viable and non-viable cells. In their study of AFB 1 , they observed that both the bacterial cell wall and its purified fragments were able to remove aflatoxin from the medium.…”
Section: Decontamination Of Aflatoxins By Lactic Acid Bacteriamentioning
confidence: 99%
“…Most interesting for the control of periodontal diseases is LAB, with antimicrobial and anti-inflammatory properties such as L. reuteri, L. fermentum, and L. casei Shirota [15,16]. Of these bacteria, L. reuteri is most interesting for the control of oral microbiota as it produces reuterin, a wide spectrum antimicrobial agent [17].…”
Section: Introductionmentioning
confidence: 99%